Severn Trent Region: River Sence, Hinlton Brook - Dunderdale, J. A. L.; Morris, J. (National Rivers Authority, 1996)
This document describes methods, results and conclusions of a study to evaluate the impacts of alternative river maintenance strategies on the River Sence and Hilton Brook in the Severn Trent Region. Its main purpose are to provide supporting information for R&D Note 456 'River Maintenance Evaluation' and to provide data which supports routines for the prioritisation and programming of river maintenance.